PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, KEPEMILIKAN INSTITUSIONAL, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERBANKAN UNIT USAHA SYARIAH - Akia, Pridatulakia; Yusmaniarti, Yusmaniarti (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to determine the effect of profitability, asset structure, institutional ownership, and liquidity on the capital structure of Islamic banking business units registered with the Financial Services Authority (OJK) for the 2018–2022 period. The research method used is descriptive quantitative with multiple linear regression analysis techniques and classical assumption testing. The results show that profitability and asset structure have a positive and significant effect on capital structure, liquidity has a negative and significant effect on capital structure, while institutional ownership has a negative but insignificant effect. The conclusion of this study is that most independent variables simultaneously influence capital structure, with a contribution of 47.7%. Keywords: Capital Structure, Profitability, Asset Structure, Institutional Ownership, Liquidity